A story about the years of political violence: "My Brother Alberto" by Jorge Ninapayta - Díaz Meléndez, Luis Jaime (2016)
In this article ask about fictional worlds of the story “Mi hermano Alberto” of Jorge Ninapayta whose genesis and implicit references have as background the years of political violence from the eighties that suffered Peru. For our approach the methodological tool of the poetry fiction inmersion developed by Ryan in her book Narrative as Virtual Reality. Inmersion and Interactivity in Literature and Electronic Media (2004); as well as the saturation function raised by Dolezel in Heterocosmica: Fiction and Possible Worlds (1999). Throeugh such instruments will seek to bring to light the constituent elements of fictional worlds to prove that “Mi hermano Alberto” is a text that with a strategic dosage of explicit and impliciti elements has a high potential to provoke the fictional inmersion of the reader and therefore to fulfill other functions transcendent of the fiction.